Perceptions of the tribal population on grama Sachivalayam (Village secretariat) concept and its services in the tribal areas of Visakhapatnam: An empirical study - Abraham, Mutluri (Journal of Contemporary Research in Social Sciences, 2023)
The Government of Andhra Pradesh historically brought a new administrative system in Andhra Pradesh on the occasion of the 150th birth anniversary of Mahatma Gandhi on 02-10-2029. The name of the system is grama sachivalayam in villages and ward sachivalayam in urban areas. A total of 11,158 village secretariats and 3,786 ward secretariats have been established across the state of Andhra Pradesh, India. The government of Andhra Pradesh recruited 1.26 lakhs various staff members and 2.8 lakh ward/village volunteers in Andhra Pradesh to run the ward/gram secretariat system. The main aim of the Grama/Ward Sachivalayam is to deliver the Navaratnalu and other state and central government welfare programmes/schemes to the poor and needy population of Andhra Pradesh. It is a new system established four years back. This is a descriptive study. The study applied a multistage sampling method and collected data from 136 tribal households through the structured interview schedule. The study found that the village secretariat system reached the grassroots levels, and agency areas and helped many tribal people living the below poverty line. The people in the tribal areas are fully satisfied with this village secretariat concept and village volunteer concept. They easily access the government welfare and development schemes at their doorsteps with the help of village volunteers. There is a lot of scope for professional social workers to develop a bridge between the government and villagers. Dealing the political pressure is a challenge to the sachivalayam staff in the selection and implementation of schemes.